Konsep Fitrah Manusia Dan Implikasinya Dalam Pendidikan Islam - Mualimin, Mualimin (Universitas Islam Negeri Raden Intan Lampung, 2017)
Human existence begins with a weakness and disability that will then move towards strength. Humans can easily utilize the grace and gift that is bestowed upon him, but man must fulfill a duty to his God. Human dignity with his Lord is not measured by how high his skill and position, his or her wealth, and his wealth. But when God measured it is his taqwa. Human beings in the Islamic perspective will remain born in a state of fithrah, that is pure, clean, free from all sin, and has the tendency to accept religion, faith, and faith. Humans become good or bad are the result of educational and environmental factors, not their original habits. According to Abd al-Rahman al-Bani quoted by an-Nahlawi states the task of Islamic education is to maintain and maintain the students' nature, then develop and prepare for all the potential possessed , by directing the nature and potential of existing and towards goodness and perfection, and realizing a program gradually. (Nahlawi, 1996) The development of human nature can be done with various learning activities. That is through an institution. The development of human nature can be done by learning activities. That is through various institutions. Learning that is not focused is through education only in school, but also can be done outside the school, whether in the family, in the community, or through the existing social science constitution.